UJI BIOAKTIVITAS EKSTRAK AKAR TABAR KEDAYAN (Aristaolochia foveolata Merr) - Siti Jubaidah; Anita Apriliana; Heri Wijaya (PROSIDING SEMINAR KIMIA, 2014)
East Kalimantan has very much plant diversity of the various ethnic Dayak. One is a plant Tabar Kedayan (Aristolochia foveolata Merr) contained in Malinau district, empirically efficacious as antidiarrheal, antidote (anti-venom), bidder alcohol for drinkers, to the efficacy of this type of p lant Aristolochia foveolata Merr not scientifically confirmed, this is because scientific research is still at least as well as the information contained bioactive compounds in the roots of Aristolochia foveolata Merr which has not been published and similarly with bio logical act ivity is not widely studied. This study aims to determine the chemical constituents of plants Tabar kedayan phytochemical screening form, which includes the bioactivity test toxicity test method Lethaly Brine Shrimp Test, antibacterial act ivity and antio xidant activity. The results of research on phytochemical screening of chemical co mpounds are alkaloids, tannins and flavonoids. Bioactivity test results on the toxicity test method BSLT 0,5,10,25 and 50 pp m concentration with the percentage of death is 0,40,60,80 and 100% level of to xicity of the ethanol extract of the roots of Tabar kedayan 7.269 ppm LC50 values obtained and included in tinggat highly toxic toxicity is 0-250 ug / ml, to test antibakter in Escherichia co li concentration of 5%, 10%, 20%, and 30% inhibition zones formed with anaverage diameter is 4.45 mm, 6.56 mm, 7.86 mm and 8.01 mm, whereas the bacterium Staphylococcus aureus is in order, with a concentration of 5%, 10%, 20% and 30% inhibition zones formed with an ave rage d iameter is 4.49 mm, 5.83 mm, 6.61 mm and 7.55 mm. Test results obtained antio xidant yellow spots after being sprayed DPPH can be concluded that the ethanol extract has antio xidant power.